Bridging the gap: Awareness and barriers to antenatal care among pregnant women in a tertiary health-care facility; single center study - Ritu Khatuja; Priya Singh; Sonal Prasad; Natasha Tyagi; Shweta Soorauthiya; Nisha Mishra; Vedanshi Verma (Asian Journal of Medical Sciences, 2025)
Background: Antenatal care (ANC) is a crucial component of maternal health services aimed at ensuring the well-being of both mother and fetus during pregnancy. Despite increased institutional deliveries and policy emphasis on maternal health, awareness and utilization of ANC services remain suboptimal in many settings, particularly among women from low socioeconomic backgrounds. Understanding these factors is essential to designing effective interventions and improving maternal and perinatal outcomes.